A novel picture fuzzy ELECTRE method and its application to long-term shelter site selection after an earthquake: The case of Antakya - Akkaya, Beril (Graduate School, 2023)
Decision-making is an essential part of human life, involving continuous choices made by individuals, institutions, and companies. While some decisions are straightforward, others are more complex and require specific methodologies to reach conclusions. These methodologies are developed to address the challenges of decision-making. Decision-making can be categorized into single and multi-criteria approaches. Decision-making environments can be classified based on the availability and certainty of information. In deterministic environments the decision-making process is fairly straightforward as the information is known and certain, whereas in risky and uncertain environments, the process becomes more challenging. In addition to these classifications, fuzzy decision-making environments address circumstances where even defining the boundaries of goals and constraints becomes a complex task. Traditional multi-criteria decision-making approaches, designed for precise information are not suitable for such problems. Fuzzy methods allow for the representation of ambiguous or imprecise information through partial memberships dissimilarly to crisp sets. Fuzzy settings have been shown to be more beneficial when dealing with problems that heavily rely on human judgement, as they account for linguistic expressions of people during the evaluation of alternatives and criteria in MCDM problems. Consequently, many MCDM methods are extended to fuzzy settings. MCDM methods encompass hierarchical approaches, multi-objective mathematical programming, and outranging methods. Outranking methods rely on pairwise comparison of criteria to determine the best alternative, or the ranking of the alternatives. Among the outranging methods, the ELECTRE methods family is widely used. They are utilized for alternative selection problems, ranking of the alternatives, and assigning them to pre-defined categories. Various fuzzy extensions of the ELECTRE methods exist, enabling the representation of vagueness and ambiguities. Picture fuzzy sets excel in representing human consideration, expressing the thoughts in terms of positivity, neutrality, negativity, and refusal. However, only ELECTRE methods integrated with other methods such as EDAS and TODIM were extended to picture fuzzy settings and a complete ELECTRE method extension has not been made. The motivation behind this thesis is to address the absence of a picture fuzzy ELECTRE method in the existing literature, despite the potential of picture fuzzy sets to capture the impreciseness in human thought. The goal of the study is to extend the ELECTRE method to the picture fuzzy environment. Additionally, the devastating earthquakes that occurred in Turkey, on February 6, 2023, serve as an additional motivation for conducting an experimental study to aid decision-making in the affected region, particularly in Hatay. The main objective of this thesis is to propose a methodology for the selection of long-term shelter site selection following this disaster along with an effective application analysis to ensure its practicality. To ensure the relevance and accuracy of the study, decision-makers from various fields of expertise related to the subject are involved. The criteria for evaluation of the problem are determined by a literature review. Criteria weights are evaluated by the experts, then criteria weights are finalized by using SWARA method. The alternative locations also proposed by a local scholar. The expert also evaluated alternatives with PiF linguistic scale to construct initial decision matrix. After the procedure of the method is completed, the best alternative for shelter site is decided as North Side of the Asi River. A sensitivity analysis by assigning different weights to different types of concordance and discordance sets and using different distance measures are performed, and the results indicates the consistency of method and the solutions. Finally, a comparative study is conducted with the TOPSIS method and MAIRCA-ELECTRE methodology.
Özgün görüntü bulanık sayı ELECTRE metodu ve deprem sonrası uzun vadeli geçici yerleşim bölgesi seçimi üzerine uygulaması: Antakya örneği
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: ELECTRE method; ELECTRE yöntemi; Multi criteria decision making; Çok kriterli karar verme